Pengaruh Kebiasaan membaca Buku Ekonomi Syariah Terhadap Pengembangan Diri mahasiswa Ekonomi Syariah: (Studi Kasus Universitas Islam Negri Sultan maulana Hasanuddin banten) - Difa ardini; Ahmad Ghondur Dhyiaul Haq; Serliani Lubis; Aufilana Rohmatika; Hadi Peristiwo; Wahyu Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to examine how the reading habits of students studying Islamic economics affect their personal growth. The task of sharia economics students is to understand economic ideas and theories that are in line with sharia law. Reading texts related to sharia economics is one approach to achieving this. Utilizing a questionnaire as a data collection tool, the research methodology is quantitative. Thirty sharia economics students were randomly selected to become the research sample. Research findings show that reading Islamic economics books regularly has a good and big impact on students' self-development in this subject. The significance value (p) of 0.000 and correlation coefficient (r) of 0.784 support this.